Caracterización y recurrencia sísmica del nido de Bucaramanga (2016)
In this paper the seismic recurrence of the Bucaramanga Seismic Nest is calculated from the analysis of seismic events in the area between May 2012 and February 2013. This analysis was carried out using the probabilistic method of synthetic seismograms complemented with a deterministic method to estimate the energy released. Also, the characterization of the area known as the “Bucaramanga Seismic Nest” was achieved. Finaly, the area is delimited with similar characteristics, the density of accumulated fault planes is determined and the high seismic activity in the area is denoted.